MANAJEMEN USER DENGAN SISTEM LIMITASI QUOTA DAN LIMITASI BANDWIDTH PADA ROUTER MIKROTIK - Yuli Praptomo PHS; M. Insan Nur Firdaus (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
The internet has played a major role in the dissemination of information and communication so that the wider range of benefits for various groups of users is also widespread, including the PT. Wahana Lintas Nusa Persada. However, the internet connection is not regulated, either the speed of access or management of the user can cause the potential to be used improperly. There is no limitation or limitation of access speed, data usage quota and user settings at PT. Wahana Lintas Nusa Persada is a problem that needs to be solved. These problems can be overcome by managing the user as well as limiting bandwidth and quota data using Mikrotik. With User Manager on Mikrotik, user management and bandwidth and quota data settings can be done. This implementation is carried out in several stages, namely user analysis and access needs of each user to determine the limits of both speed and data quota, proper and efficient system design in implementation and system testing carried out by testing methods. Based on the implementation that has been carried out, it can facilitate user management and distribution of internet connections along with the speed of access and data quota according to the needs of employees and the efficiency of their use during working hours at PT. Wahana Lintas Nusa Persada.